Characterization of 10 new tetranucleotide microsatellite markers for the European eagle owl, Bubo bubo: Useful tools for conservation strategies - Leon-Ortega, Mario (2016)
Bubo bubo is the largest owl in the world, showing a wide geographical distribution throughout the Palaearctic region. It underwent a demographic decline in many European countries during the last century and was considered “vulnerable” (Annex II of the CITES). Nowadays, it is classified as “Least Concern” according to IUCN. Despite its ecological importance and conservation status, few polymorphic molecular markers are available to study its diversity and population genetics. We report on the isolation and development of 10 new microsatellites for the Eagle owl, B. bubo. All loci (10 tetra-nucleotide) are characterized by high polymorphism levels. Number of alleles ranged from 5 to 13 and expected heterozygosity varied from 0.733 to 0.840. These microsatellites would be very useful to assess the genetic diversity, connectivity patterns and parentage of B. bubo. This information will allow to establish new conservation strategies and improve the management of the species.